(untitled) (Czech Journal of International Relations, 2004)
the European Union (1998-2000). The main research questions are: how to measure success or failure in the accession negotiations? Are the conditions of the Czech Republic’s entry well negotiated? Why are the results of the negotiations the way they are? The study demonstrates that the abilities of negotiators influence the results of the accession negotiations. This confirms the hypothesis that negotiators’ abilities, their strategy, and tactics matters in this specific and highly asymmetric negotiations, although the character of the accession negotiations would presume that those should have only minor role in the accession talks. The analysis studies the influence of the negotiators’ abilities in the good results in the area of the transitional periods as well as in the relatively less successful outcomes in the financial deal. Although a direct correlation between the effective strategy/tactics and successful results as well as between the incompetent or missing strategy/tactics and unsuccessful outcomes was not found, the study proves the impact of the individual as well as collective strategy/tactics of the candidates. The Czech Republic individually, as well as in the cooperation with other candidates, achieved not only expected minor concessions but was also able to change the original position of the EU and even the EU methodology. The strategy of the Czech foreign policy towards the bilateral disputes with the member states (nuclear power Temelín, Benes decrees) could influence the low sum of the future Czech income for the years 2004-2006 from the EU budget, although the resultant amount was mainly determined by the objective reasons in the distribution of the finances among the candidates.